1993
DOI: 10.2307/2112735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of School Restructuring on the Achievement and Engagement of Middle-grade Students

Abstract: This study examined the impact of attending restructured schools on the achievement and engagement of young adolescents. The restructuring movement is placed within the conceptual framework that favors the development of more communally organized schools, as opposed to the largely bureaucratic model of most American schools. Using a subsample of data from the base year of the National Longitudinal Study of 1988 (NELS:88), including 8,845 eighth graders in 377 public, Catholic, and independent middle-grade scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(102 citation statements)
references
References 38 publications
0
98
0
4
Order By: Relevance
“…Students in schools demonstrating fidelity to the middle school concept, for example, were found to academically outperform and exhibit fewer behavior problems than their peers in schools not implementing the middle school concept (Felner et al, 1997). Lee and Smith (1993) also found certain aspects of the middle school concept to be positively associated with students' academic achievement and engagement, and the Center for Prevention Research and Development's research suggested that implementing the middle school concept could positively impact student achievement (Mertens & Flowers, 2006;Mertens, Flowers, & Mulhall, 2002).…”
Section: Middle School Conceptmentioning
confidence: 99%
“…Students in schools demonstrating fidelity to the middle school concept, for example, were found to academically outperform and exhibit fewer behavior problems than their peers in schools not implementing the middle school concept (Felner et al, 1997). Lee and Smith (1993) also found certain aspects of the middle school concept to be positively associated with students' academic achievement and engagement, and the Center for Prevention Research and Development's research suggested that implementing the middle school concept could positively impact student achievement (Mertens & Flowers, 2006;Mertens, Flowers, & Mulhall, 2002).…”
Section: Middle School Conceptmentioning
confidence: 99%
“…25-31, for a discussion of centering). Simi larly, ß 1; captures the unique relationship between socioeconomic status and gain in achievement in school/ Socioeconomic status, affecting the child's context in the home, has consistently been shown to affect outcomes associated with school ing such as students' aspirations, interest in school, and achievement (Apple, 1979;Bowles & Gintis, 1976;Eder, 1981;Gamoran, 1996;Hollingshead, 1949;Lee & Bryk, 1989;Lee & Smith, 1993). Finally, the student-level model includes a unique error term for student i in school j, r ip indicating that each student's gain in achievement will not be perfectly predicted by the regression equation in his or her school.…”
Section: Multilevel Models: Effects Of Social Contexts At the Individmentioning
confidence: 99%
“…Coming from the student level, students' characteristics are formed on the basis of their interactions with others and their backgrounds (Apple, 1979;Bowles & Gintis, 1976;Eder, 1981;Gamoran, 1996;Hollingshead, 1949;Lee & Bryk, 1989;Lee & Smith, 1993). Much of the effect of background, such as that associated with socioeconomic status, can be considered an institutionalized aspect of the student's culture.…”
mentioning
confidence: 99%
“…There is growing evidence that student engagement, a multi-dimensional construct that Astin (1984, p. 297) defines as "total amount of physical and psychological energy that the student devotes to the academic experience," is directly related to student achievement (Carini, Kuh, & Klein, 2006;Furlong & Christenson, 2008;Lazowski & Hulleman, 2016;Lee & Smith, 1993;Willingham, Pollack, & Lewis, 2002). It is for that reason that student engagement is, itself, becoming an objective of classroom instruction.…”
Section: Introductionmentioning
confidence: 99%